An Innovative Cascade System for Simultaneous Separation of Multiple Cell Types - Pierzchalski, Arkadiusz (Public Library of Science, 2013)
Isolation of different cell types from one sample by fluorescence activated cell sorting is standard but expensive and time consuming. Magnetic separation is more cost effective and faster by but requires substantial effort. An innovative pluriBead-cascade cell isolation system (pluriSelect GmbH, Leipzig, Germany) simultaneously separates two or more different cell types. It is based on antibody-mediated binding of cells to beads of different size and their isolation with sieves of different mesh-size. For the first time, we validated the pluriSelect system for simultaneous separation of CD4+- and CD8+-cells from human EDTA-blood samples. Results were compared with those obtained by magnetic activated cell sorting (MACS; two steps -first isolation of CD4+, then restaining of the residual cell suspension with anti-human CD8+ MACS antibody followed by the second isolation). pluriSelect separation was done in whole blood, MACS separation on density gradient isolated mononuclear cells. Isolated and residual cells were immunophenotyped by 7-color 9-marker panel (CD3; CD16/56; CD4; CD8; CD14; CD19; CD45; HLA-DR) using flow cytometry. Cell count, purity, yield and viability (7-AAD exclusion) were determined. There were no significant differences between both systems regarding purity (MACS (median[range]: 92.4% [91.5-94.9] vs. pluriSelect 95% [94.9-96.8])) of CD4+ cells, however CD8+ isolation showed lower purity by MACS (74.8% [67.6-77.9], pluriSelect 89.9% [89.0-95.7]). Yield was not significantly different for CD4 (MACS 58.5% [54.1-67.5], pluriSelect 67.9% [56.8-69.8]) and for CD8 (MACS 57.2% [41.3-72.0], pluriSelect 67.2% [60.0-78.5]). Viability was slightly higher with MACS for CD4+ (98.4% [97.8-99.0], pluriSelect 94.1% [92.1-95.2]) and for CD8+-cells (98.8% [98.3-99.1], pluriSelect 86.7% [84.2-89.9]). pluriSelect separation was substantially faster than MACS (1h vs. 2.5h) and no pre-enrichment steps were necessary. In conclusion, pluriSelect is a fast, simple and gentle system for efficient simultaneous separation of two and more cell subpopulation directly from whole blood and provides a simple alternative to magnetic separation.